Secure Data Encryption Through Combination of RSA Cryptography Random Key Algorithm and Quadratic Congruential Generator - Khairina, N; Harahap, M K; Husein, A M; Muhathir; Muliono, R (Journal of physics. Conference series, 2019)
A cryptographic algorithm is used to enhance the security of the data. Algorithms whose security level is not too strong will pose a risk to data security. To safeguard the security of data, the key on the cryptographic algorithm is made as strong as possible, in order to avoid from irresponsibility parties. This paper uses the random keys for the Rivest Shamir Adleman Algorithm. The random keys that used to encrypt each plaintext letter are always different. The random key was originally formed from the first value of iteration, and it was called as seed. The seed for forming the value of p and q which generated by the Quadratic Congruential Generator Algorithm. The combination of the RSA Random Key Algorithm and the Quadratic Congruential Generator algorithm shows that each plaintext letter has own unique value of p, q, public key, and private key. This value is really always different for each encryption process. The result from this research can measure from the resistance of the cryptanalyst attack. The resistance of the RSA Random Key Algorithm toward the cryptanalyst attacks is 64 %.